2012
DOI: 10.1039/c2ib20113e
|View full text |Cite
|
Sign up to set email alerts
|

Cell Image Velocimetry (CIV): boosting the automated quantification of cell migration in wound healing assays

Abstract: Cell migration is commonly quantified by tracking the speed of the cell layer interface in wound healing assays. This quantification is often hampered by low signal to noise ratio, in particular when complex substrates are employed to emulate in vivo cell migration in geometrically complex environments. Moreover, information about the cell motion, readily available inside the migrating cell layers, is not usually harvested. We introduce Cell Image Velocimetry (CIV), a combination of cell layer segmentation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 35 publications
(66 reference statements)
3
49
0
Order By: Relevance
“…A modulation of the mechanical linkage between cells in a monolayer is essential for expedient wound healing by directed migration while preserving the sheet integrity [5,26]. Here, we demonstrated that flow-mediated wall shear stress and substrate topography cooperate to enable a dynamic control of cell-to-cell contact stability upon healing.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…A modulation of the mechanical linkage between cells in a monolayer is essential for expedient wound healing by directed migration while preserving the sheet integrity [5,26]. Here, we demonstrated that flow-mediated wall shear stress and substrate topography cooperate to enable a dynamic control of cell-to-cell contact stability upon healing.…”
Section: Discussionmentioning
confidence: 87%
“…Quantitative analysis of wound healing was performed using the Cell Image Velocimetry (CIV) Matlab toolbox [26]. Reported values are mean values over the first 7.5h (30 frames) of the experiment, considering cells inside a region extending 250 µm into the cell layer.…”
Section: Video Analysismentioning
confidence: 99%
“…In [90], a set of wound healing experiments of human umbilical vein endothelial cell (HUVEC) sheets seeded on bioengineered silicon substrates has been analyzed with Cell Image Velocimetry (CIV, a software able to combine an automated detection mechanism for tracing the migrating wound front with a flow detection tool for capturing transport processes inside the cell layer). In a complete agreement with the proposed CPM simulations, an alignment in the topography of the surface in the direction orthogonal to the wound edge has been observed to induce cell shape polarization and orientation and to lead to sustained cell migration, thereby allowing an optimal wound closure.…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of spatially varying SCE potentials, elliptically shaped potential functions or fixed bonds in-between SCEs could address these limitations. Ongoing work focuses on the coupling of particle model with experimental data [20,40,41] and the quantification of uncertainties in the force field following related work of our group on Molecular Dynamics [6].…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore important for future works to carefully calibrate such migration models with experimental data. Data from wound healing assays [20,40] or the growth of blood vessels in the mouse retina [41] could be used to fit parameters for the models and to quantify their uncertainties [6].…”
Section: Only Considering the Neighborhood Elements Of Different Cellmentioning
confidence: 99%